Key performance inficators of individual medalists in rhythmic gymnastics competing at the 2020 Olympic Games - Agopyan, A.; Ors, B. S. (Science of Gymnastics Journal, 2023)
This study aims to analyze the contribution of each apparatus' score component to the overall score and to identify the key performance indicators that distinguish medalists from non-medalists among the 10 finalists in rhythmic gymnastics at the 2020 Olympic Games, Tokyo. Medalists (n=3) and non-medalists (n=7) were separated in the sample. Each apparatus (hoop/ball/clubs/ribbon) had seven components [body difficulty (DB), apparatus difficulty (DA), D total, artistic execution (EA), execution technical (ET), E total, total score (TS) of apparatus, and a total final score (TFS-sum of four apparatus scores)]. A total of 350 scores were analyzed. The Mann-Whitney U tests and Cohen's d effect size (ES) calculation were used to calculate differences. The following variables were determined to differentiate the TFS of the medalist and the non-medalist gymnasts: the large effect with Ball-DA/D total/EA/E total/TS (ES=1.550-1.879), Clubs-DA/D total/EA/TS (ES=0.316-2.080), Hoop-DA/D total/TS (ES=1.897-2.316), Ribbon-EA (ES=1.879), and with a low-effect Clubs-AD(ES=0.316) components. Hoop-DA and Hoop-D-TS (ES=2.316, p< 0.05) have the greatest impact, while all DB and ET scores (p>0.05) have no effect on TFS. The impact of apparatus-specific score components on Olympic medal outcomes varies significantly. Notably, difficulty scores (both total and apparatus-specific) and artistic scores emerged as key performance indicators for achieving high total scores and securing a medal in rhythmic gymnastics at the Olympic Games. Coaches should prioritize choreography planning aimed at enhancing difficulty, particularly the apparatus difficulty score, while also focusing on enhancing artistic quality through flawless execution of routines by the gymnasts.